Conocimientos y actitud para la aplicación de medidas de bioseguridad en Enfermeras (o), Hospital Belén - Carhuachin Cabrera, Yoselin Elizbeth (2023)
This research is quantitative, descriptive, correlational and cross-sectional, it was carried out with nurses (os) who work in the Surgical and Surgery Center of the Hospital Belén de Trujillo (HBT), whose purpose was to determine the relationship that exists between the level knowledge and attitude for the application of biosafety measures in nurses. The sample universe was made up of 27 nurses; 2 questionnaires were used that were validated and reliable; the first was to evaluate the understanding of biosecurity measures, and consisted of 22 items (Cronbach's Alpha: value 0.825), and the second to know the attitude about biosecurity measures elaborated based on 24 evaluation items (Cronbach's Alpha : value 0.933). Each result was represented in tables, in the form of numbers and also in percentages. In order to determine the link between the variables, the "Chi-square" test was used; In addition, Spearman's correlation was used to determine the degree of relationship of the variables considered. It was found that 55.6% of the nurses had a good degree of knowledge, and 25.9% was regular. 63.0% of the nurses have a good degree of attitude, and 37.0% are regular. Concluding that both variables are significantly related